Fuzzy Controller Application in the Electrical Stimulation Development for Accelerating Wound Healing - Rahmawati; Achmad Arifin; Duti Sriwati Aziz; Gunawan; Raisah Hayati; Siti Amra (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2025)
Chronic wound healing remains a clinical challenge due to the limited capacity of conventional therapies to accelerate tissue regeneration. Electrical stimulation (ES) offers a promising therapeutic modality; however, open-loop ES cannot adaptively adjust therapy duration. This study developed a closed-loop ES system incorporating fuzzy controller to dynamically regulate stimulation duration based on wound progression. The method integrates an Atmega32-based ES platform, fuzzy controller algorithms, and preclinical testing on guinea pigs. The ES system operates at a frequency of 20 Hz, a pulse width of 250 µs, and an output voltage of 50 V. The fuzzy controller adjusts stimulation duration within a range of 15–45 minutes according to the difference between the actual and target wound areas, achieving an estimation error of 0.3%. Preclinical evaluations compared the therapeutic effectiveness of closed-loop ES, open-loop ES, and no-ES conditions. Wound-area reduction over seven days in the closed-loop group reached 64–67%, higher than the open-loop (44–50%) and no-therapy (47%) groups. Closed-loop therapy also produced the highest tissue-density outcomes (75–100%), exceeding those of the open-loop (50%) and no-therapy (25–50%) groups. The fuzzy-controlled closed-loop ES accelerated tissue regeneration by approximately 1.5–2 times compared to open-loop and no-therapy conditions. Effectiveness rankings showed the closed-loop system achieving the highest scores (0.90 and 1.00), outperforming the open-loop (0.61) and no-therapy (0.51) groups. These findings indicate that fuzzy-controlled closed-loop ES provides superior wound-healing performance compared to conventional approaches, offering a more adaptive and precise therapeutic strategy with potential for broader medical application.